Safety and Clinical Efficacy of Prostatic Artery Embolization in Patients with Indwelling Urinary Catheter for Benign Hyperplasia—A Multicenter Study - Jules Pouchot; Amandine Crombé; Luc Burlet; Fadi Farah; Pierre Baseilhac; Arthur David; François Petitpierre; Rim Maaloum; Yann Le Bras; Gaele Pagnoux; Haytham Derbel; Hicham Kobeiter; et al. (Diagnostics)
Background/Objectives: This multicentric study aimed to evaluate the efficacy and safety of prostatic artery embolization (PAE) to remove indwelling urinary catheter (IUC) in patients with symptomatic benign prostatic hyperplasia (BPH). Secondary objectives were to identify features associated with post-PAE catheter-free survival (PCFS). Methods: All consecutive patients who underwent PAE for IUC related to BPH with a follow-up of at least 2 years (except for early death) in 6 French University Hospitals were retrospectively included. Clinical efficacy was defined as the removal of the IUC after PAE (through a trial without catheter [TWOC]) and evaluated at regular intervals. Chi-square tests, Wilcoxon tests and multivariable binary logistic regressions were utilized to investigate predictors of TWOC success. Univariable and multivariable Cox regressions were utilized to investigate predictors of PCFS in patients with TWOC success. Results: 140 men with IUC (median age: 82.5 years, interquartile range [IQR] = 73–88.2 years, range: 46–100) who underwent PAE between January 2017 and March 2021 were included. Initial successful catheter removal (TWOC success) following PAE occurred in 113/140 (80.7%) patients, and 3/140 (2.1%) patients encountered major complications. In patients with TWOC success, PCFS at 6 months, 1 year and 2 years were 87.5% (95%CI: 81.4–94.1), 84.4% (95%CI: 77.7–91.7) and 79% (71.3–87.4), respectively. No independent predictive factors for TWOC success and PCFS were identified. Conclusions: PAE should be considered as a safe option with good clinical efficacy in the short and long term for elderly and inoperable patients with IUC due to symptomatic BPH.